Development of MoO3/Au/MoO3 Top Transparent Conducting Electrode for Organic Solar Cells on Opaque Substrates. Issue 2 (29th November 2021) - Pali, L. Sowjanya; Tiwari, Jeetendra Kumar; Ali, Nasir; Ghosh, Subhasis; Nalwa, Kanwar S.; Garg, Ashish
Abstract : For realization of flexible solar cells on cheap opaque substrates such as steel foils, it is vital to develop new top transparent conducting electrodes as alternatives to indium tin oxide. Such integration will also lead to a value addition of steel foils for roofing applications. This manuscript demonstrates detailed optical and electrical characteristics of a MoO3 /Au/MoO3 multilayered electrode and its integration with the organic solar cells. Improvement in the optical transmission of MoO3 /Au/MoO3 films, as studied by optical ellipsometry, suggested that higher refractive indices and lower extinction coefficients of MoO3 films compared to Au films make MoO3 an excellent choice as a capping layer for improved light coupling throughout the visible region, resulting in up to twofold improved transparency over a Au‐only film. Further, the presence of metallic Mo +4 cations present at the Au/MoO3 interface, as observed from XPS measurements, enhances the metallic nature of the MoO3 film near the Au/MoO3 interface, resulting in the reduction of the resistivity of the trilayer MoO3 /Au/MoO3, approaching twice that of ITO. Organic solar cell devices fabricated on opaque steel substrates with a MoO3 /Au/MoO3 top electrode clearly showed improvement in the photovoltaic performance by 1.5 times, compared with those obtained with single layer top metal electrodes, increasing from ≈4% to ≈6%. Abstract : 6% efficiency in an organic solar cell on opaque steel substrates using a MoO3 /Au/MoO3 electrode is demonstrated. Whilst the higher refractive index and lower extinction coefficient of MoO3 flims, compared to a Au film, makes MoO3 an excellent light coupling layer, the presence of metallic MoO +4 cations at the Au/Mo3 interface reduce the resistivity of the MoO3 /Au/MoO3 electrode making it a promising transparent conducting electrode for opaque substrates.